Active Consideration of Future Health Can Be Prompted by Simple Health Messages and Improves Nutritional Quality of Food Choices - Gustafson, Christopher R. (Frontiers in Nutrition, 2022)
Many choices that people face daily have implications for future health and wellbeing. Choices about what foods to purchase and consume are one of the most frequent—and universal choices—that people must make. The ongoing rise of overweight and obesity rates—and associated diet-related diseases—in the US and many other countries illustrates the future health consequences of low-quality dietary choices. While a large body of research shows that individuals with a tendency to consider the future make a wide range of healthier decisions, research on limited attention and exogenous factors influencing choice suggests that attention to future to the future consequences of choices may vary from one choice scenario to the next. In this research, we examine the impact of active consideration of future health impacts during a hypothetical online food choice experiment on the nutritional quality of food choices and on choice process variables—the set of products people choose to select from and the use of nutrition information during choice—during an online food choice task. Next, we examine the impact of exposure to a short message about the health benefits of fiber on consideration of future health impacts and on the nutritional quality of choices. We find that active consideration of future health impacts significantly improves the nutritional quality of choices—particularly among processed food products—and makes people more likely to pay attention to healthy foods and use nutrition information. Exposure to a short health message significantly increases the likelihood that individuals consider future health impacts during choice, which promotes healthier choices overall.